Transmigrasi Wilayah Perbatasan di Indonesia - Sukmaniar Sukmaniar; Wahyu Saputra (Universitas Negeri Makassar, 2019)
This literature review aims to examine transmigration at the Indonesian border. The research uses a literature review approach derived from research journals, scientific posters, and proceedings from seminars relating to transmigration at the Indonesian border. The results of this study can be explained that the transmigration program in Indonesia's border regions has both positive and negative impacts. Transmigration is able to contribute to the development of natural resources at the border with the skills of transmigrants so that natural resources can be utilized by border residents. The negative impact of the transmigration program is that it occurs to indigenous people who feel they are not getting enough change in their economies so that social gaps arise between indigenous people and transmigrants. Indigenous people feel that the results of their land management are not as good as those of transmigrants, resulting in inequality in income disparities that present conflict between the two. Kajian literatur ini bertujuan untuk mengkaji tentang transmigrasi di perbatasan Indonesia. Pada penelitian menggunakan pendekatan kajian literatur yang berasal dari jurnal-jurnal hasil penelitian, poster-poster ilmiah, dan prosiding dari seminar yang berkaitan tentang tranmigrasi yang ada di perbatasan Indonesia. Hasil dari studi ini dapat dijelaskan bahwa program transmigrasi di wilayah perbatasan Indonesia mempunyai dampak positif maupun dampak negatif. Transmigrasi mampu memberikan kontribusi dalam pengembangan sumber daya alam yang berada di perbatasan dengan keterampilan para transmigran sehingga sumber daya alam dapat dimanfaatkan oleh penduduk perbatasan. Dampak negatif dari program transmigrasi yaitu terjadi pada penduduk asli yang merasakan kurang mendapatkan perubahan pada perekonomiannya sehingga muncul kesenjangan sosial antara penduduk asli dengan para transmigran. Penduduk asli merasa hasil pengelolaan lahannya tidak sebaik dengan transmigran sehingga terjadi ketimpangan perbedaan pendapatan yang menghadirkan konflik diantara keduanya.